FRANÇAIS DE SPÉCIALITÉ ET FRANÇAIS SUR OBJECTIFS SPÉCIFIQUES. - APPROCHE DE L’ORAL - - Roxana-Magdalena BÂRLEA (Diversitate si Identitate Culturala in Europa)
This paper focuses on class activities based on speaking and listening within two specific teaching contexts: “languages on specific purposes” and “specialised languages”. After drawing a brief outline of the parameters that characterise these two situations, we proceed to analyse some of the elements that play a key role in creating these class activities, striving to make them as close as possible to real-life professional communication.